Temperature dependence of elastic properties of ZrB2–SiC composites. Issue 2 (1st February 2016) - Lugovy, M.; Slyunyayev, V.; Orlovskaya, N.; Mitrentsis, E.; Aneziris, C.G.; Graule, T.; Kuebler, J.
Abstract: Elastic properties (Young׳s modulus, shear modulus, and Poisson׳s ratio) of ZrB2, SiC ceramics and ZrB2 –SiC ultra high temperature ceramic composites were measured by the Impulse Excitation technique in the RT–1173 K temperature range. Two compositions of ZrB2 with 17 vol% and 32 vol% of SiC strengthening phase were hot pressed to almost full density, followed by machining before the measurements took place. The temperature dependences of elastic properties have shown the expected softening behavior, where only small 4% and 5% linear reduction in Young׳s and shear moduli were detected, respectively, for ZrB2 –17 vol% SiC and ZrB2 –32 vol% SiC ceramic composites. The reported decrease in elastic moduli brings the respective linear increase of Poisson׳s ratio up to 9% in the temperature of interest. Such high temperature behavior corresponds well to the upper and lower bounds of elastic moduli of two ZrB2 –SiC ceramic composites calculated by Voigt and Reuss estimations using properties of pure ZrB2 and pure SiC ceramics, as published in the literature.